Application of Literacy and Numeracy in Junior High School Learning - Cahyaningrum, Gyta Krisdiana; Cahyono, Didik (PT. Riset Press International, 2024)
The Numeration Literacy Program organized by the Ministry of Education and Culture and Technology in the Teaching Campus Program is a program that aims to improve the quality of education. The focus of this research examines the implementation of efforts to improve numeracy literacy skills through the 6th generation teaching campus program. This research method is a quantitative approach. The location of the study was carried out at State Junior High School 3 Tenggarong Seberang, the study population included students and teachers. Data collection using observation techniques, interviews, documentation, as well as AKM pre-test and post-test. The results showed that the implementation of the campus teaching program batch 6 through collaborative activities in the numeracy literacy application program carried out, including school making, reading movement 15 minutes before learning, language month activities, literacy teaching in class, numeracy ice breaking, numeracy snakes and ladders, Literacy Numeracy quizzes and the application of technology adaptation. The results of the implementation of the program can increase students' AKM scores on literacy by 8% and numeracy by 3%. This study concluded that the implementation of the numeracy literacy program through the 6th generation teaching campus can improve numeracy literacy skills.